Successful Management of Palatal Developmental Groove–Associated Periodontal Defect Using Palatal Access Flap and Odontoradiculoplasty: A Case Report - Nicola Alberto Valente; Giulia Bardini (Case Reports in Dentistry)
This case report discusses the successful management of a deep palatal developmental groove associated with Stage III generalized Grade C periodontitis. Despite prior nonsurgical periodontal therapy, the disease progressed rapidly, necessitating further intervention. A comprehensive evaluation revealed generalized periodontitis with localized tooth-related predisposing factor due to a developmental groove in the vital upper left lateral incisor. The initial nonsurgical treatment involved scaling and root planing (SRP) coupled with systemic antibiotics. Significant improvement was observed, except for the site with the developmental groove. Surgical intervention was performed using a palatal access flap odontoplasty and radiculoplasty to eliminate the remaining pocket and enhance plaque control. The procedure successfully resolved the condition, with soft tissue healing observed at the 6-month follow-up with a residual probing depth of 3 mm. This case highlights the challenges associated with palatal developmental grooves as localized aggravating factors in periodontitis. The use of surgical techniques like odontoplasty and flap access proved effective in managing periodontal defects associated with developmental grooves, showcasing a successful outcome in this patient.